Partisipasi Masyarakat Lokal Desa Angseri Dalam Pengelolaan Daya Tarik Wisata Air Panas Angseri, Kecamatan Baturiti, Tabanan - Saputra, Gede Mahendra; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2018)
Angseri village is located in _ Baturiti subdistrict, Tabanan regency, Bali. Angseri village has _ Angseri Hot Springs as a tourist attraction. This tourist attraction has a special characteristic than another hot springs tourist attraction. _ The special characteristic of this hot springs is in the middle of bamboo forest. The management of this hot springs started in 2007 until now and this management still running well with many involved party in it. The research that will be done is _ about how is the actual condition of Angseri hot springs reviewed on tourism product component and how is the pattern of participation in management of Angseri hot springs in Angseri village which the _ management is managed by the local community itself.                   The research method used is qualitative descriptive with in-depth interview, observation, documentation, and literature _ study. The data sources are obtained from primary and secondary data. The theory and concept used are concept of attraction, concept of management, _ concept of tourism product component, and theory of participation _ typology in management.                   The actual condition is reviewed from tourism product component located in Angseri hot springs which is an attraction that take benefit from natural potential in the form of hot springs, a n adequate access, feasible infrastructures, and the completeness of supporting facilities. In the participation typology of local community in management of Angseri hot springs, there were well organization and management structure and the participation of local community which belongs to pushed participation. In this case, the local community is given socialization by Tourism Department in the beginning of planning Angseri hot springs tourist attraction .   Keywords : Participan, Management,Product Component, Angseri Hot Springs